The Effect of Unripe Papaya Consumption on the Smooth Production of Breast Milk in Ciandam Village, Mande District, Cianjur, Indonesia - Dita Humaeroh; Erna Nurhayati (HM Publisher, 2023)
Background. Consumption of unripe papaya is one of the local wisdom which is believed to be useful in increasing the breast milk production of breastfeeding mothers. Hereditary unripe papaya has been consumed in public areas to increase milk production. This study is one of the first studies to provide scientific evidence of the effects of the unripe papaya on breast milk production in Ciandam Village, Mande District, Cianjur, Indonesia. Methods. This study was an experimental study, where as many as 30 subjects participated in this study. Data analysis was carried out using SPSS 25 in a bivariate manner to determine the effect of unripe papaya consumption on breast milk production. Results. After consumption of fruit papaya on the first day, there was increased production of Breast milk in the intervention group compared to before consumption of unripe papaya p=0.02 (p<0.05). Likewise, after the consumption of unripe papaya on the second to the seventh day, an increase in milk production was found in the intervention group compared to before the consumption of unripe papaya, p < 0.05. Conclusion. There is an influence of unripe papaya consumption on the smooth breast milk of breastfeeding mothers in Ciandam village, Mande District, Cianjur, Indonesia.